Outdoor Air Pollution and COPD-Related Emergency Department Visits, Hospital Admissions, and Mortality: A Meta-Analysis. (2nd January 2017) - DeVries, Rebecca; Kriebel, David; Sama, Susan
ABSTRACT: A systematic literature review was performed to identify all peer-reviewed literature quantifying the association between short-term exposures of particulate matter <2.5 microns (PM2.5 ), nitrogen dioxide (NO2 ), and sulfur dioxide (SO2 ) and COPD-related emergency department (ED) visits, hospital admissions (HA), and mortality. These results were then pooled for each pollutant through meta-analyses with a random effects model. Subgroup meta-analyses were explored to study the effects of selected lag/averaging times and health outcomes. A total of 37 studies satisfied our inclusion criteria, contributing to a total of approximately 1, 115, 000 COPD-related acute events (950, 000 HAs, 80, 000 EDs, and 130, 000 deaths) to our meta-estimates. An increase in PM2.5 of 10 ug/m 3 was associated with a 2.5% (95% CI: 1.6–3.4%) increased risk of COPD-related ED and HA, an increase of 10 ug/m 3 in NO2 was associated with a 4.2% (2.5–6.0%) increase, and an increase of 10 ug/m 3 in SO2 was associated with a 2.1% (0.7–3.5%) increase. The strength of these pooled effect estimates, however, varied depending on the selected lag/averaging time between exposure and outcome. Similar pooled effects were estimated for each pollutant and COPD-related mortality. These results suggest an ongoing threat to the health of COPD patients from both outdoor particulates and gaseous pollutants. Ambient outdoor concentrations of PM2.5, NO2, and SO2 were significantly and positively associated with both COPD-related morbidity and mortality.